Mācīšanās no vienaudžiem kā viena no iespējām lasītprasmes apguvē 5-6 gadu veciem bērniem pirmsskolā - Celitāne, Rasa (Latvijas Universitāte, 2022)
Darba tēma: Mācīšanās no vienaudžiem kā viena no iespējām lasītprasmes apguvē 5-6 gadu veciem bērniem pirmsskolā Darba autore: Rasa Celitāne Darba zinātniskā vadītāja: profesore, Dr. pead. Baiba Kaļķe Darba apjoms: 78 lpp. , 5 pielikumi, izmantots 60 literatūras avots Atslēgvārdi: LASĪTPRASME, VIENAUDŽI, 5-6 GADUS VECI BĒRNI. Pētījuma mērķis: izzināt, kā vienaudži var palīdzēt apgūt lasītprasmi 5-6 gadus veciem bērniem pirmsskolā. Pētījuma mērķis ir analizēt un pētīt kā vienaudži palīdz apgūt lasītprasmi.Izvirzītā mērķa sasniegšanai tika analizēta un pētīta teorētiskā literatūra par lasītprasmi un nosacījumiem tās apguvē. Papildus tika pētītas arī 5-6 gadus vecu bērnu psiholoģiskās un fizioloģiskās likumsakarības. Īpaša uzmanība tika pievērsta vienaudžu sadarbībai, lai izvērtētu tās pozitīvo ietekmi lasītprasmes sekmēšanā, un pētīts, kādi uzdevumu veidi veicina vienaudžu mācīšanos. Empīriskajā pētījumā izmantota novērošanas metode. Pētījumā iekļauts katra bērna raksturojums, apkopotas un īstenotas dažādas spēles, rotaļas, ar kuru palīdzību 12 nedēļu garumā pētīta vienaudžu ietekme lasītprasmes sekmēšanā. Pētījuma beigās visiem bērniem bija uzlabojusies lasītprasme, kas dod iespēju secināt, ka vienaudži veicina lasītprasmi ar savu piemēru, atbalstu, iedrošinājumiem un prasmi paskaidrot, kas arī sniedz pozitīvu atbildi uz pētāmo jautājumu. Pētījuma jautājums: Kā mācīšanās no vienaudžiem veicina lasītprasmi pirmskolas 3. posmā? Pētījuma metodes: novērošana Pētījuma bāze: Rīgas pilsētas pašvaldības “x” pirmsskolas izglītības iestādes desmit piecus līdz sešus gadus veci bērni.

The Topic of the Paper: Peer learning as an opportunity for acquisition of literacy in kindergarted children at 5 to 6 years The Author of the Paper: Rasa Celitāne The Supervisor of the Paper: Dr. paed. Baiba Kaļķe The Volume of the Paper: 78 pages, 5 appendices, 60 sources of reviewed literature Key Words: LITERACY, PEERS, FIVE TO SIX-YEAR-OLDS The Aim of the Research Study: to find out the ways 5 to 6-year-old peers can support one another in acquiring the reading skills at kindergarten. The aim of the research is to analyse and explore how peers aid one another in learning literacy. In order to achieve the aim, theoretical literature sources on literacy and the preconditions for its development were studied, analyzed and critically evaluated. In addition, the relationship between the physiological and pshychological development of 5 to 6-year-olds was studied. Peer collaboration was studied in particular – to assess its beneficial effect on facilitating literacy; types of exercises encouraging peer learning were identified. In the empirical research the observation method was used. In the research, the profile of each child was included; various games and plays were identified and carried out during a period of 12 weeks when peer influence on facilitating literacy development was researched. At the final stage of the research, all the children who participated in the study had improved their literacy, therefore it can be concluded that peers facilitate the development of literacy by setting a positive example, offering their support, encouragement and explanation. Thus, the outcome of the study provided a positive answer to the research question. Research Question: How does peer learning facilitate literacy development in kindergarten, Stage 3? Research Method: observation Research Base: Ten 5 to 6-year-old children of Riga City municipal preschool educational institution X ABSTRACT The Topic of the Paper: Peer learning as an opportunity for acquisition of literacy in kindergarted children at 5 to 6 years The Author of the Paper: Rasa Celitāne The Supervisor of the Paper: Dr. paed. Baiba Kaļķe The Volume of the Paper: 78 pages, 5 appendices, 60 sources of reviewed literature Key Words: LITERACY, PEERS, FIVE TO SIX-YEAR-OLDS The Aim of the Research Study: to find out the ways 5 to 6-year-old peers can support one another in acquiring the reading skills at kindergarten. The aim of the research is to analyse and explore how peers aid one another in learning literacy. In order to achieve the aim, theoretical literature sources on literacy and the preconditions for its development were studied, analyzed and critically evaluated. In addition, the relationship between the physiological and pshychological development of 5 to 6-year-olds was studied. Peer collaboration was studied in particular – to assess its beneficial effect on facilitating literacy; types of exercises encouraging peer learning were identified. In the empiri
Peer learning as an opportunity to acquire reading skills of 5 to 6 year-old children in preschool educational establishments
Keywords: Pedagoģija; lasītpramse; vienaudži; 5-6 gadus veci bērni; grupu darbs; rotaļa